Partycypatywne działania promocyjne jako czynnik budowania tożsamości regionalnej. Przykład województwa łódzkiego - Michalska-Żyła, Agnieszka; Michalska-Dominiak, Beata (Eastern Review, 2018)
The aim of the article is to present a specific approach to the problem of constructing the regional identity of the Lodzkie Region based on activities promoting the region. Attention was focused on those activities that have specific form of so-called “events”. These initiatives have, in addition, a function integrating representatives of various communities associated with the region and an educational function within the scope of ideas and methodologies of design thinking (as the big idea of the Lodzkie brand). Attention was drawn to their “out of the box” and innovative approach to the construction of regional identification.